Penggunaan Media Pembelajaran berbasis Teknologi Pada Pembelajaran Pendidikan Agama Islam Di SMK Negeri 6 Merangin - Kartika Sari; Suslinda Suslinda; Citra Elia Kartika; Irsad Alhapis; Muhammad Nuzli (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The objectives to be achieved in this study include wanting to know the use of Islamic religious education teaching materials for class XII students at SMKN 6 Merangin, wanting to know the media used in learning Islamic religious education for class XII students at SMKN 6 Merangin, and wanting to know what obstacles the pai teacher experienced in teaching Islamic religious education to class XII students at SMKN 6 Merangin. This research is a type of qualitative research with a phenomenological design. In this research, the data sources used are primary data and secondary data. The resource persons from this research were teachers of Islamic Religious Education subjects, and students of class XII Multimedia. The results showed that the teaching materials for Islamic religious education for class XII students at SMKN 6 Merangin were in fairly good condition. However, here researchers still find the ineffective use of teaching materials, because there are still many students who are not active in discussions. The learning media for Islamic religious education for class XII students of SMK N 6 Merangin are in quite good condition, namely using infocus media and internet media. However, here the author finds obstacles in its use, namely the limited facilities at SMK Negeri 6 Merangin which only has 1 infocus. Constraints found by the author in the use of teaching materials and learning media, namely the lack and limitations of book references, the use of technology that is still awkward.